Cold-Inducible SIRT6 Regulates Thermogenesis of Brown and Beige Fat - Lu Yao; Xiaona Cui; Qi Chen; Xiaoying Yang; Fude Fang; Jun Zhang; Guoqing Liu; Wanzhu Jin; Yongsheng Chang (Cell Reports, 2017)
Promoting development and function of brown and beige fat may reduce obesity. Here, we show that fat SIRT6 expression is markedly induced by cold exposure and a β-adrenergic agonist. Deletion of SIRT6 in adipose tissue impairs the thermogenic function of brown adipocytes, causing a morphological “whitening” of brown fat, reduced oxygen (O2) consumption, obesity, decreased core body temperature, and cold sensitivity. Fat SIRT6-deleted mice exhibit increased blood glucose levels, severe insulin resistance, and hepatic steatosis. Moreover, SIRT6 deficiency inhibits the browning of white adipose tissue (WAT) following cold exposure or β3-agonist treatment. Depletion of SIRT6 expression in brown adipocytes reduces expression of thermogenic genes, causing a reduction in cellular respiration. Conversely, SIRT6 overexpression in primary fat cells stimulates the thermogenic program. Mechanistically, SIRT6 interacts with and promotes phospho-ATF2 binding to the PGC-1α gene promoter to activate its expression. The present study reveals a critical role for SIRT6 in regulating thermogenesis of fat.